In situ observations of self-repairing single-walled carbon nanotubes - Boerrnert, F; Gorantla, S; Bachmatiuk, A; Warner, J; Ibrahim, I; Thomas, J; Gemming, T; Eckert, J; Cuniberti, G; Buechner, B; Ruemmeli, M (2010)
Single-walled carbon nanotubes are shown to have self-repairing capabilities exceeding that predicted by theory. Time-series aberration-corrected low-voltage transmission electron microscopy is used to study the defect dynamics of single-walled carbon nanotubes in situ. We confirm experimentally previous theoretical predictions for the agglomeration of adatoms forming protrusions and subsequent ejection. An explanation for the preferred destruction of smaller-diameter tubes is proposed. The complete healing of a ∼20 -atom multivacancy in a nanotube wall is shown while theory only predicts the healing of much smaller holes. © 2010 The American Physical Society.